PENINGKATAN KEMAMPUAN SENI LUKIS MELALUI KEGIATAN FINGER PAINTING PADA ANAK KELOMPOK B DI RA ARROHIM SUMBERBENING BRINGIN KAPUPATEN NGAWI - Eny Setiyowati Setiyowati; Eko Prasetiyo Prasetiyo; ana Setiyawati Setiyawati (Kurikula : Jurnal Pendidikan, 2022)
This study aims to determine the ability of painting through finger painting activities for group B children in RA ARROHIM Sumberbening Bringin Ngawi Regency. This study uses a classroom action research method with the subject of the Principal RA ARROHIM Sumberbening, Teacher RA ARROHIM Sumberbening, Students RA AR-Rohim Sumberbening. The results of this study the children are very enthusiastic in participating and happy when doing this activity, so that through this application it can improve children's ability to hone children's painting well. This can be seen from the beauty of the child in painting with finger painting. In the second cycle 90.9% of the children have scored in the high category, with the description that the child has been able to meet the predetermined assessment indicator criteria, and the first cycle only reached 72.7%. Keywords: artistic ability, painting, finger painting